Youtube Sebagai Media Dakwah: (Analisis Isi Pesan Dakwah Ustadz Hannan Attaki Dalam Tema “Mengatasi Sifat Yang Sering Berkeluh Kesah”) - Arfian Suryasuciramdhan; Qanitah Salma; Alaika Amaly Khaira; Rahma Aniq Aulia; Hana Zulfia (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Islam is a religion widespread throughout the world, which has its roots in Saudi Arabia, and a religion that teaches teachings that bring goodness to all mankind. Islamic da'wah is increasingly being carried out on social media, such as TikTok, Instagram, YouTube, websites and Telegram. Da'wah is the process of conveying, inviting or calling on other people or the community to embrace, learn and practice religious teachings consciously, so as to awaken and restore the person's natural potential, and be able to live happily in the world. Increased internet use cannot be avoided along with technological developments. YouTube usage continues to increase in several other countries. Ustadz Hanan Attaki, Lc., made the informant interested in the preaching delivered by Ustadz Hanan Attaki on YouTube Hanan Attaki, this is actually targeted at today's young generation because the message is delivered using millennial language and contains a moral message so that listeners can accept Ustadz Hanan Attaki's preaching . Ustadz Hanan Attaki has the ability to motivate someone without being direct.